HUBUNGAN ANTARA BELAJAR TAMBAHA DENGAN PRESTASI AKADEMIK SISWA SEKOLAH DASAR ISLAM AL-ULUM KOTA PEKANBARU - Soni Hardiyanti; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to look “ The relationship between the additional learning with elementary school students academic achievement Islam Al-Ulum Pekanbaru city ”. The hypothesis proposed in this research is the presence of a strong relathionship between the additional learning with elementary school student academic achievement Islam Al-Ulum Pekanbaru city. Population in this study were all of students in grade four and five primary school Islam Al-Ulum Pekanbaru city, where as the authors take a random sample from a population of 112 students. Research instrument was a questionnaire with the likert scale medel of choice answers a,b,c, and d. To determine the relationship between the two variables writer uses descriptive quantitative analysis manually by using simple frequency tables. The result of this study showed a strong relationship between the additional learning with elementary school students academic achievement Islam Al-Ulum Pekanbaru city with the lowest percentage of grades of 50% and the highest 21.43%.Keywords : additional study, academic achievement